New insights into gully formation on Mars: Constraints from composition as seen by MRO/CRISM - J. I. Núñez; O. S. Barnouin; S. L. Murchie; F. P. Seelos; J. A. McGovern; K. D. Seelos; D. L. Buczkowski (Geophysical Research Letters)
Abstract Over 100 Martian gully sites were analyzed using orbital data collected by the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) and High Resolution Imaging Science Experiment on the Mars Reconnaissance Orbiter (MRO). Most gullies are spectrally indistinct from their surroundings, due to mantling by dust. Where spectral information on gully sediments was obtained, a variety of mineralogies were identified. Their relationship to the source rock suggests that gully‐forming processes transported underlying material downslope. There is no evidence for specific compositions being more likely to be associated with gullies or with the formation of hydrated minerals in situ as a result of recent liquid water activity. Seasonal CO2 and H2O frosts were observed in gullies at middle to high latitudes, consistent with seasonal frost‐driven processes playing important roles in the evolution of gullies. Our results do not clearly indicate a role for long‐lived liquid water in gully formation and evolution.